2016
DOI: 10.1136/bmjopen-2015-010145
|View full text |Cite
|
Sign up to set email alerts
|

Persistent spatial clusters of high body mass index in a Swiss urban population as revealed by the 5-year GeoCoLaus longitudinal study

Abstract: ObjectiveBody mass index (BMI) may cluster in space among adults and be spatially dependent. Whether and how BMI clusters evolve over time in a population is currently unknown. We aimed to determine the spatial dependence of BMI and its 5-year evolution in a Swiss general adult urban population, taking into account the neighbourhood-level and individual-level characteristics.DesignCohort study.SettingSwiss general urban population.Participants6481 georeferenced individuals from the CoLaus cohort at baseline (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, a significant proportion of overweight or obese individuals (WHO, ) perceive themselves to be lighter than they really are (Cornelissen et al, ; Gunnare, Silliman, & Morris, ), and this underestimation is associated with underestimation of cardiovascular and personal health risks (Powell et al, ). Since obesity tends to be geographically clustered (Dahly, Gordon‐Larsen, Emch, Borja, & Adair, ; Joost et al, ; Tamura et al, ), individuals living in high obesity areas are both more likely to be obese, and more likely to be exposed to more obese bodies in their visual environment.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is no longer possible to ignore the fact that consumers are strongly attracted to food high in salt, sugar, and fats, 20 or that income and living environments affect eating habits. 21 To sum up, objective individual responsibility attribution for one's disease involves a step procedure. First we need to identify known health-related lifestyle factors (Figure 1, dark dotted zone) and estimate the extent of their explained variance.…”
Section: Limiting Factormentioning
confidence: 99%